Skala Prioritas Kewenangan Peraturan Daerah Tentang Kerja Sama Daerah Pada Sektor Perikanan Di Kabupaten Bolaang Mongondow Selatan - Suleman, Larmin; Marwan, Marwan; Insani, Nur (Jurnal Litigasi Amsir, 2025)
The fisheries sector represents a key potential in South Bolaang Mongondow Regency, but its utilization has not been optimal due to a lack of coordination and cooperation between regions. This study aims to examine the priority scale of authority in regional regulations related to regional cooperation and their impact on the fisheries sector. Using a qualitative approach through document analysis and interviews, the results indicate that priorities should include interregional cooperation, infrastructure development, fisherman capacity building, and ecosystem protection. Effective implementation requires a systematic approach through communication forums, outreach, institutional strengthening, monitoring, evaluation, and budget support.